The Effect of Using Podcast toward Students’ Listening Skill - Ghina Muthi'ah Azmi (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT This research was conducted at SMK Lab Business School Kota Tangerang. The aim was to know whether there is a significant effect of using Podcast to improve students' listening skill. The population of this research was eleventh grade students of SMK Lab Business School Kota Tangerang. The sample are 37 students of 11 AP 2. This research used Quasi-Experimental. The data was collected by pre-test and post-test. The statistical calculation of the one-sample Kolmogorov-Smirnov test was the result of this research; the asymptotic significance of the pre-test and post-test in the experimental class data is 0.000 < 0.05.It can be concluded that Ha is accepted and H0 is rejected. It means that the use of podcast on listening skill makes a significant difference. It can also be concluded that the Media Podcast has a positive impact on listening skills in the eleventh grade of SMK Lab Business School Kota Tangerang in the academic year 2020/2021.